Coup d’oeil sur la décade soixante-dix - Moreau, Rémi (Assurances, 1983)
Me Rémi Moreau has studied the annual review of the year’s results which appeared in our magazine in each of the last ten years. He believes that the reader will appreciate a general over view of insurance results for the entire decade, and we thank him for taking the trouble to study the many and varied articles of our contributors. As the reader will have noticed, each year we try to summarize the tendencies of the previous twelve months. Me Moreau's article enables us to follow the major developments in the insurance field and the opinions they evoke from our contributors.